2004
DOI: 10.1023/b:inte.0000031739.62559.ac
|View full text |Cite
|
Sign up to set email alerts
|

Value of the Congenital Hypertrophy of the Retinal Pigment Epithelium in the Diagnosis of Familial Adenomatous Polyposis

Abstract: Pigmented fundal lesions are highly pleomorphic and represent the variable expression of a common genetic defect of growth regulation. No association was found between CHRPE characteristics and specific FAP variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 37 publications
0
39
0
1
Order By: Relevance
“…CHRPE is a congenital manifestation of APC gene mutations that is not age-dependent and hence could provide a useful marker of patients with a germline APC gene mutation [31]. This possibility has been addressed on a number of occasions and by different means with conflicting outcomes [9,16,[19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CHRPE is a congenital manifestation of APC gene mutations that is not age-dependent and hence could provide a useful marker of patients with a germline APC gene mutation [31]. This possibility has been addressed on a number of occasions and by different means with conflicting outcomes [9,16,[19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, pigmented retinal lesions occurred commonly in both control and test subjects and the distinction between CHRPE and other pigmented lesions was not always simple. Furthermore, small pigmented ''dots'' are frequent in fundus examinations in the general population [16,36], especially in the far periphery where retina is thin and there may be varying degrees of pigmentation from the underlying dark choroid. These do not have clinical significance in the context of CHRPEs and FAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that there is no association between CHRPE characteristics and FAP phenotype variants [7] . It was reported that the rate of CHRPE is 75%-80% in Western FAP patients [8] and 93.75% in Chinese FAP families.…”
Section: Discussionmentioning
confidence: 98%
“…Mutations downstream of codon 1,596 are frequently seen in AFAP (11). Mutations between codons 1,445 and 1,578 were associated with desmoid tumors, whereas those between codons 279 and 1,309 were correlated with the development of duodenal polyposis (22)(23)(24). While it appears promising to predict a patient's phenotype by the mutation site of the APC gene, this was proven to not be feasible in clinical practice.…”
Section: Discussionmentioning
confidence: 99%